Fever and Antipyretic Supported by Traditional Chinese Medicine: A Multi-Pathway Regulation - Ma, Le-Le; Liu, Hui-Min; Luo, Chuan-Hong; He, Ya-Nan; Wang, Fang; Huang, Hao-Zhou; Han, Li; Yang, Ming; Xu, Run-Chun; Zhang, Ding-Kun (Frontiers in Pharmacology, 2021)
The coronavirus disease, 2019 (COVID-19), has spread rapidly around the world and become a major public health problem facing the world. Traditional Chinese medicine (TCM) has been fully committed to treat COVID-19 in China. It improved the clinical symptoms of patients and reduced the mortality rate. In light of the fever was identified as one of leading clinical features of COVID-19, this paper will first analyze the material basis of fever, including pyrogenic cytokines and a variety of the mediators of fever. Then the humoral and neural pathways of fever signal transmission will be described. The scattered evidences about fever recorded in recent years are connected in series. On this basis, the understanding of fever is further deepened from the aspects of pathology and physiology. Finally, combining with the chemical composition and pharmacological action of available TCM, we analyzed the mechanisms of TCMs to play the antipyretic effect through multiple ways. So as to further provide the basis for the research of antipyretic compound preparations of TCMs and explore the potential medicines for the prevention and treatment of COVID-19.